Superheroes [videorecording (DVD)] : a never-ending battle - Kantor, Michael, 1961-; Schreiber, Liev (PBS Distribution, 2013)
Examines the dawn of the comic book genre and its progenitors, as well as the evolution of the characters that leapt from the pages over the last 70 years and their ongoing worldwide cultural impact. It chronicles how these 'disposable diversions' were subject to intense government scrutiny for their influence on American children and how they were created in large part by immigrants whose fierce loyalty to a new homeland laid the foundation of a multi-billion-dollar industry.